PENGARUH CITRA TOKO DAN KUALITAS PELAYANAN TERHADAP KEPERCAYAAN PELANGGAN SERTA NIAT BELI PRODUK PRIVATE LABEL ALFAMART - Wiratama, I Gede; Rahyuda, Ketut; Kerti Yasa, Ni Nyoman (Buletin Studi Ekonomi; VOL.22.NO.2. AGUSTUS 2017 (PP 113-261), 2017)
Alfamart is one of the biggest retail company in Indonesia that has private label products as a corporate competitive strategy. The sales of Alfamart’s private label products still below the national products. Therefore, the company should develop internal and external strategies to increase customer purchase intention toward Alfamart’s private label products.The purpose of this study was to describe the effects of store image and service quality to customer trust and purchase intentions toward private label products. This study used 200 respondents with purposive sampling technique and analyzed by Structural Equation Modeling (SEM). The results showed that the effects of store image and service quality were significantly positive on customer trust and customer purchase intention, as well as the effect of customer trust was significantly positive on customer purchase intention. Research implication showed that the organization should manage internal and external factor to increase purchase intention. Keywords: store image, service quality, customer trust, purchase intention